prove that:(1) v=u+at (2) s=it+1/2at² (3)2as=v²-u²
Answers
Answered by
17
Derivation of equation of motion
For One dimensional motion with a = constant
We can write,
Where a = constant
Integrating both side , we get
At t = 0 , Velocity is u and at t = t velocity is v Hence
Hence proved
Now we can write
At time t = 0 Suppose s=0 and at t = t , displacement is a
Hence proved
Again we can write as
When s = 0 , v is u and at s = s , velocity is v . Therefore
Hence proved
Similar questions
Biology,
4 months ago
Math,
4 months ago
Science,
4 months ago
Social Sciences,
7 months ago
Social Sciences,
1 year ago
Political Science,
1 year ago
Math,
1 year ago